Neurobehavioral Aspects of the Delayed Encephalopathy of Carbon Monoxide Intoxication: Case Report and Review - M. F. Mendez; R. C. Doss (Behavioural Neurology)
We report the neurobehavioral aspects of the delayed encephalopathy of carbon monoxide (CO) intoxication in a 29 year old woman and review the literature. Four weeks after CO poisoning, the patient developed a frontal lobe syndrome, visuoperceptual impairment, and diffuse white matter lesions with an otherwise normal neurological examination. In contrast, patients with the classical syndrome also have a parkinsonian state or an akinetic–mute state. The delayed encephalopathy of CO poisoning usually results from demyelination of subcortical white matter, necrosis of the globus pallidus, or both. The clinical aspects, risk factors, neurobiological features, and therapy and prognosis are discussed.